Speech-Language Pathology Practice Advancement: The Influence Of Research And Evidence-Based Practice On Staying Current - Ashekian Kalfayan, Taline
Speech pathology is a quickly evolving field as new research and discoveries may deem past practices old as newer practices prove to be more efficient in improving speech in patients. It is a speech therapist’s job to learn current practices by taking courses and continuing their education, as well as exploring practices and techniques, different from their own, from other professionals to use any resource available to ensure the best treatment for their patients. Speech pathologists can continue their education through various methods, including but not limited to continuing medical education (CME) or continuing professional development (CPD) programs, conferences and workshops, and online courses/webinars. Most countries, including the U.S., require speech pathologists to take continuing education courses to reach a certain number of credits every few years to be able to maintain their licenses and continue their practice. Although many countries require pathologists to continue their education, there may still be challenges including time and financial constraints as some courses can cost up to $700. However, the benefits of continuing education and learning to modify old patient practices to fit new research far outweigh the challenges that may come with it. It is crucial for countries like Armenia that do not have a strict policy for continuing education to modernize their medical education system and ensure that speech pathologists stay up to date on their medical knowledge and be able to help patients efficiently and effectively.
Keywords: continuing education